Taḥlīl al-Khitāb al-Tamāsuk wa al-Tarābuṭ fi al-Kitāb Durūs al-Lugah al-Arabiyah a’lā al-Țarīqati al-Ḥadīśah al-Juz' al-Śānī lil Imām Zarkasyi wa Imām Syubāni - Wahyu Dwi Saksono; Erlina Erlina; Fachrul Ghazi (KURAS Institute, 2023)
Discourse is a series of sentences or speech, namely the principle of cohesion which is the link between the different elements in a grammatical structure, then the principle of coherence, which is the relationship between the elements in a complete unit. This research focused on grammatical cohesion and coherence. The research methodology used is a library search. To obtain information and deepen theory, the researcher integrated content analysis research methods. The data collection method is the method of documenting any printed data. The method used for verification is credibility. The results of this study are. In the context of grammatical cohesion element there are three elements in the books of Durūs al-Lugah al-Arabiyah a’lā al-Țarīqati al-Ḥadīśah al-Juz' al-Śānī of Imam Zarakshi and Imam Shubani. First is the reference in two models, pronoun and demonstrative. There are fourteen pronouns and six demonstratives. The second is substitution. There are four substitutions in the book. The third is conjunction. There are four conjunctions, temporal conjunction, coordinating conjunction, correlative conjunction, and adversative conjunction. In the coherence context, there are ten elements, condition, sequential, method, deduction, time, explanation, cause and effect, addition, increase or affirmations, and resistance.